Does being too specific too young produce good youth athletes but poor adult athletes? - Sleiman, M. E. (Journal of Australian Strength and Conditioning, 2019)
Early sport specialization may not be the safest nor most effective approach for reaching the highest level of competition as an adult athlete and achieving long-term athlete development.